Experimental study on the influence mechanism of micro-abrasive air jet machining on the surface quality of Ti-6Al-4V titanium alloy formed by selective laser melting. (December 2022) - Shi, Wentian; Li, Jihang; Yuan, Meixia; Li, Quanlai; Liu, Yude; Lin, Yuxiang
Abstract: This experiment studied the effect and mechanism of micro-abrasive air jet machining (AAJ) on the surface quality of SLM-formed TC4 titanium alloy specimens under different air pressures and jet angles. The results showed that the width of the AAJ processing area increased with the increase of air pressure but decreased with the increase of the injection angle. The surface quality of SLM samples could be improved effectively by AAJ processing. The optimized percentage of surface roughness value (Sa) was the largest, reaching 54 % when the injection angle was 60 ᵒ and the air pressure was 0.5 MPa; The surface hardness of the sample increased the maximum percentage, reaching 22 % when the injection angle was 75 ᵒ, and the air pressure was 0.5 MPa. The initial abrasive grains mainly had three shapes: flake, block, and column. The flaky abrasive grains had sharp edges, a good effect on matrix removal, large processing area but shallow depth of action; The block abrasive particles were mainly removed by extrusion and accompanied by severe friction with the substrate, and layered chips were generated; The columnar abrasive grains mainly scratched the surface of the substrate to generate scratches. The material's erosion rate (ER) was the largest, reaching 1.3 %, and the processing efficiency was the highest when the injection angle was 60ᵒ and the air pressure was 0.4 MPa. The α′ martensite near the sample's surface was elongated by AAJ processing, and the direction was parallel to the sample's surface. The depth of processing influence was the largest, reaching about 30 µm when the injection angle was 75 ᵒ and the air pressure was 0.5 MPa. Graphical Abstract: ga1